Eric Nicholas K's answer to Kathy's Secondary 4 A Maths Singapore question.

done {{ upvoteCount }} Upvotes
clear {{ downvoteCount * -1 }} Downvotes
Eric Nicholas K
Eric Nicholas K's answer
3322 answers (Tutor Details)
Here are my answers. For the second question last part, it’s a lot easier (to observe) if you let a = ln r and b = ln s, so that (ln s) / (ln r) plus (ln r) / (ln s) = b/a + a/b.
Eric Nicholas K
Eric Nicholas K
5 months ago
Also note that (ln s)^2 is NOT the same as ln s^2.

i.e. ln s^2 = 2 ln s
but (ln s)^2 is NOT equal to 2 ln s